ドキソルビシン誘発心毒性の有機カチオントランスポーターOCT3欠損またはL-ヒスチジン投与による抑制効果 - 薬師神, 芳洋; 下川, 哲哉; 山下, 雅大; 山内, 広平; 前門戸, 任; 首藤, 政親; 清井, 武志; 田村, 晴希; 山田, ありさ; 小笠原, 正人; 前山, 一隆 (日本薬理学会年会要旨集, 2019)
Doxorubicin (DOX) for treatment of patients with neoplasms shows cardiac toxicity. Recent studies reported that histamine H2 receptor antagonist improved DOX-induced cardiotoxicity, while histamine deficiency exacerbates myocardial injury. To elucidate the effects and mechanisms of histamine on DOX-induced acute cardiotoxity, we investigated the cardiac functions, pathological alterations, and protein expressions of Hsp25, LAMP-1, Beclin-1, p62, LC3B, histamine H1 and H2 receptors using both mice with organic cation transporter-3 (OCT3) deficiency and mice with supplementation of L-histidine that is converted to histamine via histidine decarboxylase. The DOX-induced acute cardiotoxicity was improved in both mice by analyzing cardiac function with echocardiography and electron microscopy. The higher content of histamine, decreased histamine H2 receptor expression in basal levels, improvements of autophagy-lysosome flow, and enhancement of Hsp25 protein expression were shown in OCT3(-/-) deficiency and mice with supplementation of L-histidine. In conclusion, OCT3 deficiency and supplementation of L-histidine significantly contributes to DOX-induced acute cardiotoxicity.